2021
DOI: 10.1002/mren.202100020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Poisons Originating from Chemically Recycled Plastic Waste on the Performance of Ziegler–Natta Catalysts

Abstract: Chemically recycled monomer feed streams from postconsumer plastic packaging waste are expected to contain impurities that act as catalyst poisons. This work investigates the impact of such impurities on a commercial fourth‐generation Ziegler–Natta catalyst system. A recycled monomer feed stream in two different procedures by adding representative catalyst poisons (pyridine and n‐butanol) in various quantities to the reactor setup is simulated. Measuring catalyst activity and molecular weight distribution (MWD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…A detailed description of the reactor setup can be found in previous publications. [26,15] In order to minimize possible contaminant interference, the reactor was cleaned before each experiment using three cycles of nitrogen purging followed by evacuation the reactor. To remove remaining traces of moisture, 80 g propane was filled into the reactor, which was then heated to > 90 °C for at least 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the reactor setup can be found in previous publications. [26,15] In order to minimize possible contaminant interference, the reactor was cleaned before each experiment using three cycles of nitrogen purging followed by evacuation the reactor. To remove remaining traces of moisture, 80 g propane was filled into the reactor, which was then heated to > 90 °C for at least 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The MWDs of all samples were deconvoluted using the Flory-Schultz distribution as described in the literature. [15][16][17][18][19] In addition, the CCD (comonomer composition distribution) was calculated using the Stockmayer bivariate distribution. [16][17][18][19] The comonomer molar fractions were subsequently calculated for each site type individually.…”
Section: Mwd Deconvolutionmentioning
confidence: 99%
“…In general, using the Levenberg Marquardt minimization method, the MWD curves are fitted to 4–6 active centres until a minimum is found. [ 9–11 ]…”
Section: Introductionmentioning
confidence: 99%
“…In general, using the Levenberg Marquardt minimization method, the MWD curves are fitted to 4-6 active centres until a minimum is found. [9][10][11] Building on these studies and on our previous work, [12][13][14] we explored extensively the influence of the titanation temperature during catalyst synthesis on the microstructure and the incorporation distribution of the comonomer in LLDPE samples (Figure 1). Varying the titanation temperature over a broad range, we found that it is possible to synthesize catalysts that produce a more uniform comonomer incorporation distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Though it is a wellknown fact that these catalysts are sensitive to impurities, there are not many studies that quantified the impact of some common poisons on the catalyst activity for the latest supported Ziegler-Natta generations in gas phase polymerizations, nor investigated the consequences on the polymer microstructure and powder morphology, though such studies are currently of more interest due to the growing interest in monomers produced via chemical recycling of plastics which would contain more contaminants in comparison to conventionally produced monomers. [1][2][3] In this introduction, we will take a brief look at the few publications that have investigated the effects of poisons on propylene polymerizations experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%